Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan (Studi pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Nia Mawarsih (Akuntansi dan Manajemen, 2016)
This study aims to determine the effect of intellectual capital on the company's financial performance. The independent variable used in this study is intellectual capital. The dependent variable used in this study is the company's financial performance as measured by Return on Assets (ROA). Return on Equity (ROE) and Growth of Revenue (GR). The research sample is a pharmaceutical company that is listed on the Indonesia Stock Exchange (IDX) with a study period of 2010-2014. Data was collected by purposive sampling method, based on these criteria, as many as 8 companies were selected as samples in this study. The analysis technique used is simple linear regression analysis using SPSS v.20 software. the test shows that (1) intellectual capital has an effect on ROA, (2) intellectual capital has an effect on ROE (3) intellectual capital does not affect GR.